Gyrification abnormalities in presymptomatic c9orf72 expansion carriers. Issue 9 (11th May 2019) - Caverzasi, Eduardo; Battistella, Giovanni; Chu, Stephanie A; Rosen, Howie; Zanto, Theodore P; Karydas, Anna; Shwe, Wendy; Coppola, Giovanni; Geschwind, Daniel H; Rademakers, Rosa; Miller, Bruce L; Gorno-Tempini, Maria Luisa; et al.
Abstract : Objective: To investigate in-vivo cortical gyrification patterns measured by the local gyrification index (lGI) in presymptomatic c9orf72 expansion carriers compared with healthy controls, and investigate relationships between lGI and cortical thickness, an established morphometric measure of neurodegeneration. Methods: We assessed cortical gyrification and thickness patterns in a cohort of 15 presymptomatic c9orf72 expansion carriers (age 43.7 ± 10.2 years, 9 females) compared with 67 (age 42.4 ± 12.4 years, 36 females) age and sex matched healthy controls using the dedicated Freesurfer pipeline. Results: Compared with controls, presymptomatic carriers showed significantly lower lGI in left frontal and right parieto-occipital regions. Interestingly, those areas with abnormal gyrification in presymptomatic carriers showed no concomitant cortical thickness abnormality. Overall, for both presymptomatic carriers and healthy controls, gyrification and cortical thickness measures were not correlated, suggesting that gyrification captures a feature distinct from cortical thickness. Conclusions: Presymptomatic c9orf72 expansion carriers show regions of abnormally low gyrification as early as their 30s, decades before expected symptom onset. Cortical gyrification represents a novel grey matter metric distinctive from grey matter thickness or volume and detects differences in presymptomatic carriers at an early age.